Chapter Le metafore di intensificazione in russo: la realizzazione linguistica del concetto di COMPLETEZZA - Benigni, Valentina (Biblioteca di Studi Slavistici, 2018)
Adopting a data based approach, the study explores Russian intensifying metaphors of COMPLETENESS. A wide range of instantiations of the metaphor of COMPLETENESS is analyzed within the framework of Conceptual Metaphor Theory (Lakoff & Johnson 1980), comprising achievement of a result (soveršennyj idiot), filled container (nabityj durak) and round form (kruglyj otličnik). The contrastive perspective (Russian-English-Italian) provides new insights on the mapping of the source domain of COMPLETENESS onto the target domain of INTENSITY in different languages and cultures.